1995
DOI: 10.1088/0029-5515/35/3/i03
|View full text |Cite
|
Sign up to set email alerts
|

High beta discharges with neutral beam injection in CHS

Abstract: High beta plasmas with a volume averaged equilibrium beta value of 2.1% were produced in CHS using tangential neutral beam injection. This beta value was achieved with the confinement improvement (reheat mode) observed after turning off strong gas puffing. Wall conditioning with titanium gettering was used to make high density operation (ne ⩽ 8 × 1019 m-3) possible for low magnetic fields (Bt = 0.6 T). The discharges start with the magnetic hill configuration (in vacuum) and finally achieve Mercier stable equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…With respect to the Shafranov shift, the studies in W7-AS and LHD, but also in CHS [16], have shown a good agreement with 3D equilibrium code calculations with VMEC, HINT and PIES. In particular, the partial optimization of the W7-AS configuration resulting in reduced Shafranov shift could be verified [1].…”
Section: Ms-313705 Final Papersupporting
confidence: 55%
See 1 more Smart Citation
“…With respect to the Shafranov shift, the studies in W7-AS and LHD, but also in CHS [16], have shown a good agreement with 3D equilibrium code calculations with VMEC, HINT and PIES. In particular, the partial optimization of the W7-AS configuration resulting in reduced Shafranov shift could be verified [1].…”
Section: Ms-313705 Final Papersupporting
confidence: 55%
“…Before start of LHD operation, beta values in the 1.5 -2 % range have been reported by several stellarator experiments including Heliotron-E [14], the Advanced Torsatron Facility ATF [15], the Compact Helical System CHS [16] and W7-AS. Here, we are focusing on more recent results from W7-AS and LHD.…”
Section: Progress Of High-β Operation In Stellarators / Helical Systemsmentioning
confidence: 98%
“…This density dependence is a feature of anomalous transport, because strong density dependence is also observed in the energy transport, which is governed by anomalous transport. In fact, the global energy confinement shows strong density dependence in CHS, 11 as predicted by LHD scaling 12 ( E ϭ0.17P abs The differences between the parallel viscosity in the original paper and the toroidal viscosity in this paper are discussed. The approximations made in the original paper were a replacement of the Fourier series with (1/M ) ϫ(n -"B/B) and the replacement of toroidal viscosity with parallel viscosity (B ϷB) and (B -"B)/BϷn -"B).…”
Section: Discussionmentioning
confidence: 65%
“…A capability of high-␤ equilibrium is, therefore, expected for the CHS; the highest beta of 2% was achieved. 41 The CHS has a pair of four-turn windings of helical coils to generate its essential confinement field. The magnetic field configuration has a rotational symmetry of 45 degrees.…”
Section: B Compact Helical Systemmentioning
confidence: 99%